Hubungan Karakteristik Ibu Hamil Dengan Kunjungan 6 Kali (K6) Pada Usia Kehamilan Lebih Dari 36 Minggu Di Desa Gaya Baru 2 Kabupaten Lampung Tengah - Winarsih; Suryaningsih (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: K6 coverage at Puskesmas Seputih Surabaya below the target of 65.47% and Gaya Baru 2 Village K6 38.33%. K6 coverage illustrates the low quality of services for pregnant women. Incomplete pregnancy examinations can cause pregnancy complications in mothers to go undetected, increasing maternal and neonatal morbidity and mortality rates during pregnancy, childbirth and postpartum. Factors that influence antenatal care visits in pregnant women include the characteristics of the pregnant women themselves.Purpose: to analyze the relationship between the characteristics of pregnant women with 6x visits (K6) at a gestational age of more than 36 weeks in Gaya Baru 2 Village, Central Lampung Regency.Method: The research design quantitative analytic with retrospective cohort design. The research sample totaling 89 pregnant women. The object was age, parity, education, occupation, and K6 visits using a cheklist sheet research instrument with a documentation study technique of pregnant women's registers. Results: data analysis obtained the results of most pregnant women with ages 20-35 years (64%), multiparous parity (49.4%), primary education level (64%), not working (58.4%) and K6 visits not according to standards (62.9%). The correlation between age and K6 visits (p value: 0.000), parity (p value: 0.793), maternal education (p value: 0.001), and work (p value: 0.216).Conclusion: the study showed that the characteristics of age and mother's education level were related while parity and mother's occupation were not related to K6 visits.Keywords: age, parity, education, occupation, and K6 visits